Genomic scarring score predicts the response to PARP inhibitors in non-small cell lung cancer - Katerina Tsilingiri; Anna Chalari; Georgia Christopoulou; Alexandra Voutsina; Pantelis Constantoulakis; Κonstantinos Potaris; Ioannis Vamvakaris; Dora Hatzidaki; Georgina Zachou; Giannis Vatsellas; Vassilis Georgoulias; Athanasios Kotsakis; et al. (npj Precision Oncology)
Abstract PARP inhibitors (PARPi) have shown efficacy in tumours harbouring mutations in homologous recombination repair (HRR) genes. Somatic HRR mutations have been described in patients with Non-Small Cell Lung Cancer (NSCLC), but PARP inhibitors (PARPi) are not yet a therapeutic option. Here we assessed the homologous recombination status of early-stage NSCLC and explored the therapeutic benefit of PARPi in preclinical models. The Genomic Scarring Score GSS (GSS) and HRR mutation profile of 136 patients were assessed. High GSS (h-GSS) was observed in 39 (28.7%) patients half of which carried pathogenic/likely pathogenic somatic HRR mutations. TP53 mutations were significantly enriched in h-GSS tumours (p < 0.001). Olaparib significantly delayed tumour growth in h-GSS but not l-GSS Patient-derived Xenografts (PDXs), while patients with h-GSS/TP53mut tumours respond favourably to adjuvant platinum-based chemotherapy. Our functional data clearly support the idea that the use of GSS rather than the mutational status of HRR genes could select patients for administration of PARPi.